The Microbiome: What Will the Future Hold? - Monsour, Howard Paul, Jr.; Quigley, Eamonn M. M. (Seminars in Liver Disease, 2016)
Current research on the human microbiome has opened our eyes to the intimate relationship that we have with the bacteria that populate our gastrointestinal tract and its potential relationship to health and disease. To date, clinical research on the microbiome has identified intriguing associations between an altered microbiome and disease states, but proven therapeutic applications have been very limited. The ingestion of prebiotics, probiotics, and/or synbiotics is appealing to the general public and has significant commercial value, but as yet, solid evidence for clinical efficacy in liver disease has been lacking due, in large part, to the paucity of high-quality clinical trials. On the other hand, the resounding success of fecal microbiota transplantation in Clostridium difficile infection has opened our eyes to the real potential of “pharmabiotics” and may well provide an intriguing template for the development of novel approaches to modulate the microbiome and its interactions with the host and thereby treat and/or prevent disease states. We will attempt to examine the current state of microbiome therapeutics and predict how these approaches might fit into the management of liver diseases in the future.
Keywords: microbiome; pharmabiotics; diet; fecal microbiota transplantation